Conventional and Advanced Biomass Gasification Power Plants Designed for Cogeneration Purpose. (December 2015) - Perna, A.; Minutillo, M.; Cicconardi, S.P.; Jannelli, E.; Scarfogliero, S.
Abstract: In this paper conventional and advanced biomass gasification power plants designed for small cogeneration application are defined. The CHP plants consist of a gasification unit, that employs a downdraft gasifier, and a power unit based on a microturbine in the case of conventional configuration, and on a solid oxide fuel cell module, in the case of advanced configuration. The plants are sized to supply about 100 kW of electrical power. In order to investigate and to analyze the performances of the two plant configurations, in terms of thermal and electrical efficiencies, numerical models have been developed by using thermochemical and thermodynamic codes.